2021
DOI: 10.1038/s41598-021-95359-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between CETP polymorphism and dietary insulin index and load in relation to cardiovascular risk factors in diabetic adults

Abstract: Gene–diet interactions may play an important role in the inter individual diversity observed in on cardiovascular disease (CVD) risk factors. Therefore, in the current study, we examined the interaction of CETP TaqB1 polymorphism with dietary insulin index and load (DII and DIL), in altering on CVD risk factors among type 2 diabetes mellitus (T2DM). In this cross-sectional study, blood samples were collected from 220 type 2 diabetic patients (134 females and 86 male) with a mean age of 52.24 years in Tehran, I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Environmental factors, such as dietary consumption, genetic variations, and their interactions, have an impact on blood lipid levels 12 15 . Dietary changes could impact the oxidation profile of patients with various clinical diseases including diabetes, dyslipidemia, and CVDs, which are affected by foods and diets including polyphenols, flavonoids, PUFAs, and the Mediterranean diet 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as dietary consumption, genetic variations, and their interactions, have an impact on blood lipid levels 12 15 . Dietary changes could impact the oxidation profile of patients with various clinical diseases including diabetes, dyslipidemia, and CVDs, which are affected by foods and diets including polyphenols, flavonoids, PUFAs, and the Mediterranean diet 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Serum lipid levels (TC, LDL-C, HDL-C, and TG) were measured by enzymatic method (using kits from Pars Azmoon Co., Iran) [ 52 ]. The level of ghrelin and leptin were measured by the ELISA method (Bioassay Technology Co, China, and Germany) [ 53 ]. TAC measurement evaluating the overall antioxidants capacity in the body was measured by spectrophotometry and SOD levels which showes enzymatic antioxidant activity [ 54 ] was assessed using colorimetry methods (Cayman Chemical Company, USA) based on the conversion of xanthine oxidase to xanthine and O2 into uric acid and hydrogen peroxide to produce superoxide ions.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 Although carbohydrates almost completely causes the insulin response, additional nutrients such as dietary protein and lipids can influence insulin production. 25,26 Dietary insulin load and insulin index (DIL and DII) have caused much interest in this area among all the different models for predicting diet's insulinaemic ability 27,28 ; the findings from epidemiological studies have found these indices are more reliable indicators of observed insulin responses to composite meals than other methods. 29 However, no research has looked into DIL or DII in relation to people's genotypes.…”
Section: Introductionmentioning
confidence: 99%